Alumina Template-Dependant Growth of Cobalt Nanowire Arrays - L. Malferrari; A. Jagminienė; G. P. Veronese; F. Odorici; M. Cuffiani; A. Jagminas (Journal of Nanotechnology)
Different electrochemical regimes and porous alumina were applied for template synthesis of cobalt nanowire (nw) arrays, revealing several peculiar cases. In contrast to quite uniform filling of sulfuric acid alumina templates by alternating current deposition, nonuniform growth of the Co nw tufts and mushrooms was obtained for the case of oxalic acid templates. We showed herein for the first time that such configurations arise from the spontaneous growth of cobalt nw groups evolving from the cobalt balls at the Al/alumina interface. Nevertheless, the uniform growth of densely packed cobalt nw arrays, up to tens of micrometers in length, was obtained via long-term direct current galvanostatic deposition at low current density using oxalic acid templates one-side coated by conducting layer. The unique point of this regime is the formation of hexagonal lattice Co nws with a preferred (100) growth direction.